Mechano-sensitive nociceptors are required to detect heat pain thresholds and cowhage itch in human skin - Weinkauf, Benjamin; Ham, Jasper van der; Benrath, Justus; Schmelz, Martin; Rukwied, Roman (European journal of pain, 2016)
Background Mechano-sensitive and mechano-insensitive C-nociceptors in human skin differ in receptive field sizes and electrical excitation thresholds, but their distinct functional roles are yet unclear. Methods After blocking the lateral femoral cutaneous nerve (NCFL) in eight healthy male subjects (3-mL Naropin® 1%), we mapped the skin innervation territory being anaesthetic to mechanical pin prick but sensitive to painful transcutaneous electrical stimuli. Such ‘differentially anaesthetic zones’ indicated that the functional innervation with mechano-sensitive nociceptors was absent but the innervation with mechano-insensitive nociceptors remained intact. In these areas, we explored heat pain thresholds, low pH-induced pain, cowhage- and histamine-induced itch, and axon reflex flare. Results In differentially anaesthetic skin, heat pain thresholds were above the cut-off of 50°C (non-anaesthetized skin 47 ± 0.4°C). Pain ratings to 30 μL pH 4 injections were reduced compared to non-anaesthetized skin (48 ± 9 vs. 79 ± 6 VAS; p < 0.01). The axon reflex flare area did not differ between these zones (7.8 ± 1.4 cm2 vs. 8.3 ± 0.5 cm2). Histamine iontophoresis still caused pruritus in differentially anaesthetized skin in five of eight subjects (VAS 26 ± 14), whereas itch upon cowhage spicules was absent (VAS 0 vs. 29 ± 11 in non-anaesthetized skin). Conclusions We conclude that activation of mechano-insensitive nociceptors is sufficient to provoke itch by histamine- and acid-induced pain. The mechano-sensitive nociceptors are crucial for cowhage-induced itch and for the assessment of heat pain thresholds.